'The ideological tree is always green': Norberto Bobbio and the future of ideology studies. Issue 3 (2nd September 2022) - Blackburn, Dean
ABSTRACT: This article locates Norberto Bobbio within the field of ideology studies. After historicising Bobbio's contribution to the study of ideas, it reflects on some of the key themes that punctuated his work. In doing so, it shows how many of Bobbio's concepts and ideas can be used to evaluate recent political change. Not only can Bobbio help us to understand our 'age of uncertainty', but he can also be used as a point of reference when we try to historicise phenomena like populism.